Between the Legal Qualification of Climate Claims and the Law Applicable to Their Resolution from the Perspective of Polish Law .......... 111 - Krystman-Rydlewicz, Martyna (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
The legal community is increasingly seeking legal frameworks to support successful climate claims. However, the results are mixed, as the law often lacks adequate tools for effective climate action. Consequently, this chapter aims to explore whether it is legally feasible to file successful climate claims against private actors under Polish law, and if so, how to determine the applicable law for resolving such claims. Consequently, the analysis is focused on the relationship between climate change on one hand, and legal solutions, including personality rights, and tortious liability, on the other. Concurrently the multitude of legal bases for eventual claims triggers the difficulties in choosing the applicable law for the settlement of transnational climate disputes, i.e. whether their resolution should be based on the rules developed within national law or the relevant EU regulations, especially Rome II.